Women’s Property, Mobility, and Decisionmaking: Evidence from Rural Karnataka, India - Swaminathan, Hema; Lahoti, Rahul; Suchita, J. Y. (International Food Policy Research Institute, 2012)
In this paper, we examine the impact of rural women’s property ownership on their mobility and autonomy in decisionmaking. The results are based on data collected by the authors in the state of Karnataka, India (The Karnataka Household Asset Survey 2010–11), which has individual-level asset ownership and valuation information. The research was undertaken in order to measure the extent of gender disparities in asset ownership and wealth in the state, and to build on the empirical literature that discusses the importance of asset ownership for women.